Persicaria wugongshanensis (Polygonaceae: Persicarieae), an odoriferous and distylous new species from Jiangxi, eastern China - Li, Bo (Phytotaxa, 2014)
Persicaria wugongshanensis, a new species from Wugongshan Mountain, Jiangxi Province in eastern China, is described and illustrated. The new species is a distinctively odoriferous herb characterized by having glandular leaves and tepals, stout inflorescences, dimorphic flowers, extraordinarily long pedicels and densely pitted achenes. A morphological comparison among the new species and its putative relatives, P. hydropiper, P. japonica, P. jucunda and P. odorata, is presented. Comparative micromorphological characters of achenes, leaves, pollen grains and tepals of the new species and its closest relative P. odorata were also presented. Distyly and its ancillary dimorphism were observed and described. The somatic chromosome number (2n = 20) and karyotype formula (2n = 14 m + 6 sm) of the new species were reported.